(untitled) (Annals of Medicine and Medical Sciences, 2025)
Leadership in emergency medicine (EM) is crucial for ensuring optimal patient outcomes, particularly in the high-pressure, fast-paced environment of the emergency department (ED). This review examines the essential leadership qualities necessary for effective EM practice, with a specific focus on both international and Indian studies. Key leadership traits include clinical expertise, decision-making, communication, teamwork, adaptability, emotional intelligence, conflict resolution, situational awareness, and mentorship. In India, emergency medicine faces unique challenges such as resource limitations, overcrowded EDs, and a hierarchical healthcare system, all of which demand adaptable and ethical leadership. Indian studies highlight decision-making, communication, emotional intelligence, and the educational role of leaders as critical in overcoming these challenges. Despite systemic and cultural barriers, formal leadership training programs and mentorship initiatives are proposed as effective strategies to develop future EM leaders in India. The review underscores the importance of fostering a culture of continuous learning and collaboration to address the evolving needs of emergency care in India.